2000
DOI: 10.1021/ja0006144
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Surface-Exposed and Copper-Coordinating Histidine in Blue Copper Proteins:  The Electron-Transfer and Redox-Coupled Ligand Binding Properties of His117Gly Azurin

Abstract: In many reduced blue copper proteins the C-terminal surface-exposed active-site histidine protonates at low pH and dissociates from the Cu atom. In this state, the proteins exhibit high reduction potentials and low oxidation rates. In contrast, the homologous histidine (117) of azurin does not protonate. This difference has been examined by studying the electrochemical behavior of an azurin mutant in which histidine 117 is replaced by glycine to create a cavity enabling external ligands to enter the protein an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
102
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(107 citation statements)
references
References 52 publications
5
102
0
Order By: Relevance
“…The eluted dimer fraction was colorless, compatible with the copper being in the reduced state. The copper could not be reoxidized with potassium ferricyanide to the Cu(II) form as could have been expected for a H117G azurin variant (6,9). The possibility for the dimer being in its apo form is not likely because reconstitution with copper could not be achieved.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The eluted dimer fraction was colorless, compatible with the copper being in the reduced state. The copper could not be reoxidized with potassium ferricyanide to the Cu(II) form as could have been expected for a H117G azurin variant (6,9). The possibility for the dimer being in its apo form is not likely because reconstitution with copper could not be achieved.…”
Section: Resultsmentioning
confidence: 99%
“…The extinction coefficient of the absorption at 385 nm in H117G/N42C azurin has been estimated from the ratio of the absorptions at 385 nm of the Cu-H117G/N42C azurin and 280 nm of the H117G/N42C apoazurin. For the extinction coefficient at 280 nm the value of H117G apoazurin has been used (⑀ 280 ϭ 9.1 ϫ 10 3 M Ϫ1 cm Ϫ1 ) (9). Samples were measured in 20 mM HEPES, pH 7, unless stated otherwise.…”
Section: Methodsmentioning
confidence: 99%
“…Loop mutation experiments have shown that, in most cases, lengthening the ligand-containing loop lowers the His ligand pK a (9,10,12,38), whereas loop contraction increases the value (8,11,12). In AZ, the His-117 ligand does not protonate in the accessible pH range, and a pK a of Ͻ2 has been calculated (20). In the Cu(I) AZAMI loop-contraction variant, the pK a of His-115 is 5.5 [this pK a is lower than the value of 6.4 for His-96 in Cu(I) AMI] (21,38).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In particular, dicopper complexes coordinated by histidine N-donor and S-containing thiolate or sulfide ligands comprise the active sites of key metalloproteins. 4,5 Accordingly, an approach to the structure and functions of the copper centers is to develop model dicopper-multidentate ligand systems incorporating N and S donors. 6 Recently, Hanton et al 7 introduced a flexible ligand with four thiopyridyl arms L [1,2,4,5-tetrakis(2-pyridylmethylsufanylmethyl)benzene] which forms a dinuclear complex with Cd(NO 3 ) 2 instead of a polymeric array due to the unusual three-layered π-stacking motif.…”
mentioning
confidence: 99%
“…In this paper, we report two binuclear complexes [Cu 2 L(ClO 4 (2), which were structurally characterized by single-crystal X-ray analysis.…”
mentioning
confidence: 99%